Pengembangan Augmented Reality Untuk Pengenalan Huruf Hijaiyah Bagi Anak Pra Sekolah - Kamal, Zuma Fahmi; Ikrimach, Ikrimach (STMIK Banjarbaru, 2023)
Understanding Hijaiyah letters is the first step in preparing to read the Qur'an, the holy book of Islam. For this reason, interesting learning is needed to increase interest in reading Hijaiyah letters during childhood. Choosing the right learning media method is very important. In this study, the focus is on the utilization of augmented reality technology is developed and able to provide an improved solution for Hijaiyah Letter Recognition with an Application that visualizes Hijaiyah letters into a 3D representation so that the visual appearance is more attractive. They apply a method called